Characterization and expression of the wall-associated kinase/wall-associated kinase-like (WAK/WAKL) family in response to Botrytis cinerea infection in strawberry (Fragaria×ananassa) - Chenyang Xu; Zhimin He; Xiaoru Kang; Yanwei Zhao; Qingqing Peng; Min Wen; Jiaqi Yan (BMC Plant Biology)
Abstract Background Gray mold caused by Botrytis cinerea is a major threat to the production of strawberry. An increasing number of studies have reported that wall-associated kinase/wall-associated kinase-like (WAK/WAKL) played an important role in the recognition of oligogalacturonic acids (OGs) and the induction of plant defense, but there have been no systematic studies of FaWAK/FaWAKL in strawberry. Results In this study, we identified 167 FaWAK/FaWAKL gene family members within the strawberry (Fragaria×ananassa) genome. The phylogenetic analysis showed the FaWAK/FaWAKL gene family has been divided into five groups, and they were unevenly distributed on 46 chromosomes. An analysis of the cis-regulatory elements suggested the FaWAK/FaWAKL gene family was more sensitive to abscisic acid and methyl jasmonate. A total of 36 FaWAK/FaWAKL genes were activated by B. cinerea according to an RNA-seq analysis, and 8 of them strongly responded to B. cinerea and exogenous treatment with OGs, particularly FaWAK35. Transient overexpression of FaWAK35 increased the strawberry resistance to B. cinerea. Conclusion This study conducted a comprehensive analysis of FaWAK/FaWAKL and provides foundational insights for further exploration of FaWAK/FaWAKL genes in strawberry resistance to B. cinerea.